The dominant microorganisms vary with aggregates sizes in promoting soil carbon accumulation under straw application. Issue 1 (2nd January 2023) - Lu, Jinjing; Li, Shengping; Wu, Xueping; Liang, Guopeng; Gao, Chunhua; Li, Jianhua; Jin, Dongsheng; Wang, Bisheng; Zhang, Mengni; Zheng, Fengjun; Degré, Aurore
ABSTRACT: Unraveling the influence of microbes on C content at aggregate scale is pivotal for promoting soil C accumulation. Previous studies were based mainly on the mutual transformation process between aggregates, the links between the microorganisms in initial aggregates and inner C content and aggregate sizes were still unclear. In this study, the classified aggregates (> 5 mm, 2–5 mm, 1–2 mm, 0.25–1 mm, and < 0.25 mm) were individually incubated for 10 months under 13 C-labeled maize straw application to analyze the relationship between microbial community structure in independent aggregates and inner C accumulation under straw addition. The results show that the SOC content increased in independent aggregates under straw addition, with higher stable C accumulation in < 0.25 mm than in > 2 mm aggregates. Aggregates of > 5 mm were more capable of improving unstable C accumulation and C derived from straw (Cstraw ) than smaller aggregates. Fungi and Gram-negative bacteria (G-) were more important to increasing C accumulation in > 2 mm aggregates, whereas Gram-positive (G+) bacteria dominated in < 2 mm aggregates. The results indicate that the contribution of microorganisms within aggregates to inner C accumulation was associated with aggregate sizes.